Toxicity evaluation of zinc aluminium levodopa nanocomposite via oral routes in repeated dose study - Kura, Aminu Umar; Cheah, Pike See; Hussein, Mohd Zobir; Hassan, Zurina; Tengku Azmi, Tengku Ibrahim; Hussein, Nor Fuzina; Fakurazi, Sharida (SpringerOpen, 2014)
Nanotechnology, through nanomedicine, allowed drugs to be manipulated into nanoscale sizes for delivery to the different parts of the body, at the same time, retaining the valuable pharmacological properties of the drugs. However, efficient drug delivery and excellent release potential of these delivery systems may be hindered by possible untoward side effects. In this study, the sub-acute toxicity of oral zinc aluminium nanocomposite with and without levodopa was assessed using the Organization for Economic Co-operation and Development guidelines. No sign or symptom of toxicity was observed in orally treated rats with the nanocomposite at 5 and 500 mg/kg concentrations. Body weight gain, feeding, water intake, general survival and organosomatic index were not significantly different between control and treatment groups. Aspartate aminotransferase (AST) in 500 mg/kg levodopa nanocomposite (169 ± 30 U/L), 5 mg/kg levodopa nanocomposite (172 ± 49 U/L), and 500 mg/kg layered double hydroxides (LDH) nanocomposite (175 ± 25 U/L) were notably elevated compared to controls (143 ± 05 U/L); but the difference were not significant (p > 0.05). However, the differences in aspartate aminotransferase/alanine aminotransferase (AST/ALT) ratio of 500 mg/kg levodopa nanocomposite (0.32 ± 0.12) and 500 mg/kg LDH nanocomposite (0.34 ± 0.12) were statistically significant (p < 0.05) compared to the control (0.51 ± 0.07). Histology of the liver, spleen and brain was found to be of similar morphology in both control and experimental groups. The kidneys of 500-mg/kg-treated rats with levodopa nanocomposite and LDH nanocomposite were found to have slight inflammatory changes, notably leukocyte infiltration around the glomeruli. The ultra-structure of the neurons from the substantia nigra of nanocomposite-exposed group was similar to those receiving only normal saline. The observed result has suggested possible liver and renal toxicity in orally administered levodopa intercalated nanocomposite; it is also dose-dependent that needs further assessment.